Beyond Looking for the Rewarded Target: The Effects of Reward on Attention in Search Tasks - Walle, Annabelle; Druey, Michel D. (Frontiers in Psychology, 2021)
One puzzling result in training-test paradigms is that effects of reward-associated stimuli on attention are often seen in test, but not in training (e.g., Roper et al., 2014). We focus on one study (Sha & Jiang, 2016), where reward-related performance benefits occur in the training and which was discussed contentiously (Anderson & Halpern, 2017). By using a similar design, we conceptually replicated the results. Moreover, we investigated the underlying mechanisms and processes resulting in these reward-related performance benefits. In two experiments, using search tasks and having participants perform the tasks either with or without individually adjusted time pressure, we disentangled the mechanisms and processes contributing to the reward-related benefits. We found evidence that search efficiency is increased with increasing reward, but also that non-search factors contribute to the results. By also investigating response time distributions we were able to show that reward-related performance effects increased as search time increased in demanding tasks, but not in less demanding tasks. Theoretical implications of the results regarding how reward influences attentional processing are discussed.